The Local Wisdom on Language Politeness Education in the Use of PO-5 Philosophy in Buton Community: Ethnopedagogical Study - Ridwan Amsyah; Mochammad Rizki Juanda (Hasanuddin University, 2022)
This study aims to reveal the relationship between the concept of politeness from experts and the concept of politeness in the PO-5 philosophy along with its implementation and language evidence for the implementation of the PO-5 philosophy. This descriptive qualitative research used 10 conversations as the data of the study. The data collection was carried out in three ways, they are literature study, interview, and observation. The results of this research indicated that the philosophy of PO-5 is part of the local wisdoms of the Buton Islands Community where the findings consisted of 3 data of Pobhinci-bhinciki kuli, 6 data of pomae-maeaka, 4 data of pomaa-masiaka, 2 data of popia-piara, and 1 data of poangka-angkataka. The PO-5 philosophy contains many moral educations for community, one of them is related to language politeness. Philosophy of PO-5 has similarities with the maxim model of Geoffrey Leech (1993). The similarities are found between maxim of tact and Pobhinci-bhinciki kuli, maxim of generosity and pomae-maeaka, maxim of sympathy and Pomaa-maasiaka, maxim of agreement and popia-piara, and maxim of approbation and poangka-angkataka